2011
DOI: 10.15376/biores.6.4.isroi
|View full text |Cite
|
Sign up to set email alerts
|

Biological pretreatment of lignocelluloses with white-rot fungi and its applications: A review

Abstract: Lignocellulosic carbohydrates, i.e. cellulose and hemicellulose, have abundant potential as feedstock for production of biofuels and chemicals. However, these carbohydrates are generally infiltrated by lignin. Breakdown of the lignin barrier will alter lignocelluloses structures and make the carbohydrates accessible for more efficient bioconversion. White-rot fungi produce ligninolytic enzymes (lignin peroxidase, manganese peroxidase, and laccase) and efficiently mineralise lignin into CO2 and H2O. Biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Large differences within enzymatic activities detected in pretreated lignocellulosic substrates have been previously observed in several fungi, including all strains of this work [5,17,18,23]. As previously pointed out [36], this highlights the need to interpret the pattern of enzymatic activities detected as a function of interactions among fungal strains, substrates type and incubation periods.…”
Section: Fungal Pretreatment Of Chestnut Shells: Oxidative and Hydrol...supporting
confidence: 74%
See 2 more Smart Citations
“…Large differences within enzymatic activities detected in pretreated lignocellulosic substrates have been previously observed in several fungi, including all strains of this work [5,17,18,23]. As previously pointed out [36], this highlights the need to interpret the pattern of enzymatic activities detected as a function of interactions among fungal strains, substrates type and incubation periods.…”
Section: Fungal Pretreatment Of Chestnut Shells: Oxidative and Hydrol...supporting
confidence: 74%
“…More recently, VP was also isolated from fungal strains of genera Trametes [ 32 ], Phlebia [ 33 ], Ganoderma [ 34 ] and Irpex [ 35 ]. Taking into account that an efficient lignocellulosic pretreatment enhances enzyme accessibility and subsequent saccharification of structural polysaccharides [ 10 , 11 , 12 , 36 ], fungi should excrete an appropriated enzymatic balance between oxidoreductases and hydrolases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the nonselective white rot fungi biodegrade all components of lignocellulose equally (Hatakka and Hammel, 2010;Isroi et al, 2011). Among the white rot fungi that have been used for biodegradation of lignocellulose are Phanerochaete chrysoporium; Pleurotus ostreatus, Lentinus squarrosulus, Pycnoporus cinnarbariunus, Cyathus stercolerus, Ceriporiopsis subvermispora and Ceriporia lacerate, as reported by the recent studies conducted by Kumar and Sharma, (2017); Ganash et al, (2021).…”
Section: Introductionmentioning
confidence: 85%
“…Basidiomycete fungi are forest decomposers exhibiting lignocellulosic decomposing ability, while some, such as yeast, exhibit fermentability and can produce ethanol from lignocellulosic biomass [22][23][24][25][26]. Furthermore, several studies have focused on the fermentability of wild basidiomycete fungi and revealed that ethanol can be produced from unused resources, such as rice straw, wheat bran, kitchen waste, whey, and expired milk [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%